2023
DOI: 10.1002/adfm.202312316
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering White Light Emission in Pressure‐Treated Sb‐Doped Double Perovskite by Coherent Optical Phonon

Jutao Jiang,
Guangming Niu,
Xiaowei Wang
et al.

Abstract: Single‐component white‐light emitters are ideal for solid‐state lighting applications. Here, the dual‐emission white light in the 3D Cs2NaInCl6:0.1 Sb3+ crystal is successfully achieved by the high‐pressure treatment strategy. Upon compression, the remarkable self‐trapped exciton (STE) emission enhancement is observed at 20.6 GPa due to the tilting and twisting of inorganic octahedron caused by the phase transition of Cs2NaInCl6:0.1 Sb3+ crystal. Intriguingly, after undergoing the high‐pressure treatment, in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Recently, lead-free perovskites, such as double perovskites and low-dimensional perovskites, have attracted great interest in realizing excitation-dependent emission due to several intrinsic advantages including high photoluminescence quantum yields (PLQYs), low-toxicity, and low-cost solution processing. These systems possess unique soft lattices and strong quantum confinement, which endow them with broadband self-trapped exciton (STE) emission. The existence of multiple emission centers, including STEs, ligands, and doping ions, renders them a perfect platform to achieve excitation-dependent emission. For example, Kuang et al reported a zero-dimensional (0D) indium–antimony alloyed halide perovskite, BAPPIn 1.996 Sb 0.004 Cl 10 , which emits bright yellow light and white light with PLQYs of ca. 100 and 44% at 320 and 365 nm excitation, respectively .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, lead-free perovskites, such as double perovskites and low-dimensional perovskites, have attracted great interest in realizing excitation-dependent emission due to several intrinsic advantages including high photoluminescence quantum yields (PLQYs), low-toxicity, and low-cost solution processing. These systems possess unique soft lattices and strong quantum confinement, which endow them with broadband self-trapped exciton (STE) emission. The existence of multiple emission centers, including STEs, ligands, and doping ions, renders them a perfect platform to achieve excitation-dependent emission. For example, Kuang et al reported a zero-dimensional (0D) indium–antimony alloyed halide perovskite, BAPPIn 1.996 Sb 0.004 Cl 10 , which emits bright yellow light and white light with PLQYs of ca. 100 and 44% at 320 and 365 nm excitation, respectively .…”
Section: Introductionmentioning
confidence: 99%
“…The realization of dual-emission white light in the three-dimensional Cs 2 NaInCl 6 :0.1 Sb 3+ crystal was accomplished through a high-pressure treatment strategy . The observed intense Raman scattering in Cs 2 NaInCl 6 :0.1 Sb 3+ crystals underscore the robust coupling between electrons and Raman-active lattice vibrations.…”
mentioning
confidence: 99%